Resource economics an economic approach to natural resource and environmental policy - Bergstrom, John C. (Cheltenham Edward Elgar Publishing, 2016)
Resource Economics' engages students and practitioners in natural resource and environmental issues from both local and global standpoints. The 4th edition of this approachable but rigorous text provides a new focus on risk and uncertainty as well as new applications that address the effect of new energy technologies on scarcity and climate change mitigation and adaptation, while preserving and systematically updating the approach and key features that drew many thousands of readers to the first three editions.
Includes bibliographical references and indexes.
Keywords: Nonrenewable natural resources